A ANALYSIS OF MOTOR VEHICLE TAX CALCULATIONS AT THE SIDENRENG RAPPANG DISTRICT SAMSAT OFFICE - Yusra Qayyum; Andi Sri Kumala Putri P; Lisra Lisra (Journal Of Accounting And Finance, 2024)
The purpouse of this research is to find out and analyze the calculation of 2 wheeled motor vehicle tax at the Sidenreng Rappang District Samsat Office, whether the results are in accordance with tax regulations and the tax revenue results are effective. The formulation of the problem in this research is how the results of calculating 2 wheeled motor vehicle tax at the Sidenreng Rappang Samsat Office are the result are in accordance with tax provisions and tax revenue is effective. The method used in this research uses mixed methods using a descriptive approach. The data used is primary data and secondary data. Primary data is in the form of interviews and secondary data is in the form of attachments obtained from the Samsat Official of Sidenreng Rappang district. The results of the research show that the motor vehicle tax calculationc carried out at the Samsat Office in Sidenreng Rappang district is in accordance with the Regional Regulation of the Governor of South Sulawesi Number 10 of 2010 concerning Regional Taxes. The level of effectivenes of motor vehicle tax revenue has an average value of 98.75%. This value is still categorized as very effective.